Research in Women's Public Office Positions in Islam - Asar, A. K.; Ghalia, Bouhedda (International Journal of Science and Research (IJSR), 2015)
As far as research in the field of women’s public office in Islāmic jurisprudence is concerned, a number of research studies have been examined from various sources. Analysis of the literature shows that fanatic adherence to preferred mad͟hāhib (sections of fiqh) which normally confined to the views of local culture is the main factor of the disagreement. Another factor is the lack of profound understanding of the controversial nuṣūṣ (legal texts) which are related to the issue.